THE EFFECT OF SCRIBE VIDEO MEDIA ON STUDENTS' INTEREST AND LEARNING OUTCOMES ON HUMAN DIGESTIVE ORGANS MATERIAL IN CLASS V OF SDKE 32 UKKE'E SOPPENG REGENCY - Sulfian Sulfian; Muhiddin Muhiddin; Evi Ristiana (Universitas Tadulako, 2020)
This study aims to determine the effect of video scribe on students' interest and learning Outcomes in digestive organ material in humans in class V of elementary school. The research was conducted at 32 Ukke'e State Elementary School, Pesse Village, Donri-donri District, Soppeng District. The research method is Quasi Experiment with pretest and posttest control group design. The study population is all fifth grade students consisting of 2 classifications while the research sample is taken from 2 classes which are grouped into experimental and control classes. Data collection is done by taking the value of student learning outcomes or the value of filling out the interest in learning questionnaire for each class. Prior to the data analysis, the normality and homogeneity tests were first performed and then analyzed using two independent samples t-test with a significance level of 0.05 using SPSS 21 for windows.